"Sketch", "What it takes to keep the mind going" and "Drag(a) de mama" - Burghelea, Clara (Pivot: A Journal of Interdisciplinary Studies and Thought, 2023)
These poems address the manner in which white space lives in harmony with words or in the margins/ in between the lines of the poems. A good portion of meaning is found outside the written words; together with line breaks they teach the reader how to read the poems out loud and inside their minds. In these poems, white space plays several roles: it is a stylistic technique, it asks the reader to actively read the poem, and it visually creates an aesthetic.